Revision of subgenera of Stenichnus Thomson, with review of Australo-Pacific species (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2013)
Subgenera of the speciose ant-like stone beetle genus Stenichnus Thomson are revised. The genus is re-classified and only two subgenera are retained: Stenichnus s. str. and Scydmaenichnus Reitter. Two remaining subgenera, Austrostenichnus Franz and Scydmaenilla King, are elevated to the genus rank (the status of Scydmaenilla, originally described as a genus and later reduced to a subgenus of Stenichnus, is restored). Two species occurring in New Zealand, Stenichnus insignis (Broun) and Stenichnus kuschelianus Franz, previously classified in Stenichnus (Austrostenichnus), are placed in a separate genus Zeanichnus gen. nov. (with Scydmaenus insignis Broun as a type species). Scydmaenilla is divided into two subgenera: Scydmaenilla s. str. and Scydmaenillunia subg. nov. (with Scydmaenilla adelaidensis Franz as a type species). Lectotypes are designated for Stenichnus (Scydmaenichnus) fossifrons Reitter, Scydmaenilla pusilla King and Scydmaenilla constricta Lea. All Australo-Pacific species, previously placed in Stenichnus, are redescribed: Austrostenichnus caledonicus Franz (New Caledonia), Zeanichnus insignis (Broun) comb. nov. (New Zealand), Zeanichnus kuschelianus (Franz) comb. nov. (New Zealand), Scydmaenilla (s. str.) pusilla King, stat. rest. (Australia), S. (s. str.) constricta Lea, stat. rest. (Tasmania), S. (s. str.) queenslandica Franz (Australia), S. (s. str.) thompsoniana Franz (Australia), S. (s. str.) brisbanensis Franz (Australia), S. (s. str.) sydneyana Franz (Australia), and S. (Scydmaenillunia) adelaidensis Franz (Australia). A possible synonymy of Scydmaenilla queenslandica and S. thompsoniana is discussed, not possible to verify on the basis of the available material.